Question Number 114480 by mohammad17 last updated on 19/Sep/20

Commented bymohammad17 last updated on 19/Sep/20

help me sir

Answered by john santu last updated on 19/Sep/20

(4) 2y+x = 2(−1)+(2)          2y+x = 0 ; y = −(1/2)x  (5) 8x−y=8(7)−(1)          8x−y = 55 ; y = 8x−55

Commented bymohammad17 last updated on 19/Sep/20

thank you sir

Answered by Dwaipayan Shikari last updated on 19/Sep/20

2x−y=1  y=2x+1  m=2  m_0 =−(1/m)=−(1/2)  y=−(1/2).x+C  −1=−1+C  C=0  y=−(1/2)x⇒2y+x=0

Commented bymohammad17 last updated on 19/Sep/20

thank you sir

Answered by mathmax by abdo last updated on 19/Sep/20

let d  : y =mx +p      A(2,−1) ∈d ⇒−1=2m+p ⇒p =−1−2m ⇒  d    y =mx−2m−1    we have  Δ  2x−y =1 ⇒y =2x+1  d perpendicular to Δ ⇒2m =−1 ⇒m=−(1/2) ⇒  d→y =−(x/2) −2(−(1/2))−1 =−(x/2) ⇒2y=−x ⇒x+2y =0 ⇒  d→x+2y =0